P9: MANAGEMENT OF ESOPHAGEAL FOOD BOLUS OBSTRUCTION AT A UNIVERSITY TEACHING HOSPITAL – A RETROSPECTIVE ANALYSIS. (27th April 2021) - Hashmi, ZZ; Ahmed, R; Alijarad, F; Madanur, M; Razzaq, Z; Majeed, M; Bughio, M; Cagney, D; Aakif, M; Mustafa, H; Amin, A; Khan, A; et al.
Abstract: Introduction: Despite the fact that esophageal food bolus obstruction is a common surgical problem, there are no clear guidelines on its management. Medical treatment with Buscopan and Glucagon is mostly in-effective, requiring a therapeutic Oesophago-Gastro-Duodenoscopy (OGD). Method: All consecutive cases of food bolus obstructions (FBO) presenting to the Emergency Department (ED) for 18 month period between 01/01/2018 and 30/06/2019 were retrospectively reviewed. Result: A total of 30 patients were admitted with food bolus obstruction via ED (1.67 per month). Females (67%) constituted most of these patients. Average age was 55 with range of 19-83. 84% of patients presented with Dysphagia, while Odynophagia (10%) and chest pain (6%) were other presenting symptoms. Average duration of symptoms was 17 hours (Range 2 – 48 hours). 44% of patients had OGD done under sedation while others (56%) had under General Anaesthesia (GA). In 70% of cases, food bolus was pushed into stomach, while it was retrieved out in 20%. In 10%, it had already spontaneously passed in stomach on OGD. The etiology of FBO was inflammatory in 60% cases, while an esophageal stricture was seen in 10% only. In 30% cases no cause of FBO was identified. Post-OGD length of stay was on average 1.15 days (range 12 hours – 7 days). 2 patients had aspiration pneumonia prolonging their hospital stay, there was no esophageal perforation or mortality. Conclusion: Esophageal food bolus obstruction is a common surgical problem, OGD under GA is a safe recommended procedure, which often picks up an underlying pathology. Take-home message: Esophageal food bolus obstruction is a common surgical problem, OGD under GA is a safe recommended procedure, which often picks up an underlying pathology.